Does industry funding differ between men and women in electrophysiology and devices research?. (24th May 2021) - Camm, CJF; Crawford, W; Olivarius-Mcallister, J; Prachee, I; Schaefer, A; Raouf, Z; Bello, A; Ginks, M; Nicol, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: A significant gender bias has been identified in cardiology. Industry funding may be important developing electrophysiology (EP) and devices research. Such funding leads to potential conflicts of interest (COI) which must be disclosed on research presentations. There is limited evidence whether the gender bias in cardiology extends to industry funding of research. Purpose To assess whether COI disclosures in EP and devices presentations at the ESC Annual Congress differ between men and women. Methods: Recorded presentations from the Arrhythmia & Devices section of ESC Annual Congresses 2016-2020 were assessed. Presentations were excluded if the original presentation contained no slides, it was a panel discussion, it was a non-scientific presentation, or part of the presentation was missing. Presentations with multiple speakers were also excluded. Chi-squared and Mann-Whitney U tests were used to assess differences between groups for dichotomous and continuous data respectively. Results: Of 1, 153 presentations assessed, 999 were suitable for inclusion. Women made up 22% (n = 221) of presenters. There was no difference in whether COI declaration slides were missing between women (5.9%, n = 13) and men (7.6%, n = 56), p = 0.38. In those with COI disclosure slides (n = 927), women declared significantly lower median number of COIs (0, IQR 0-3) compared with men (2, IQR 0-8), p < 0.0001. In contrast, women spent a greater time-per-word on their COI disclosure slides (250ms, IQR 125-375ms) compared with men (200ms, IQR 118-333ms), p < 0.0001. Conclusions: Women made up a minority of presenters in EP/devices talks at the ESC annual congress. Women were less likely to have COIs which may suggest that they are less likely to receive industry funding. Despite this, women spent a greater amount of time-per-word on their COI slides. The lower number of declared COIs in women highlights another potential area of gender bias in cardiology that needs further investigation so that it can be addressed.